Research on Marketing Strategy of Cultural and Creative Products of Beijing Palace Museum - Zhu, Jia (Transactions on Social Science, Education and Humanities Research, 2024)
Museums have evolved over the past several years from being places to store historically significant and worthy of study cultural artifacts to being multipurpose spaces for collection exhibition, information sharing, public education, and leisure and entertainment. In order to better realize its multi-faceted functions and bring better services and experiences to visitors, the museum has gradually researched and designed a number of cultural and creative products. In order to explore the benefits of the Palace’s cultural and creative products in terms of product, price, promotion, and channels, as well as to suggest specific countermeasures from the four dimensions, this paper will investigate the marketing strategies of the cultural and creative products of the Palace Museum in Beijing. It will do this by combining empirical methods and literature research with the 4P theory. The purpose of this study is to provide some reference values for the further development of the Palace’s cultural and creative products and the marketing of other museums’ cultural and creative products in China, and to promote the healthy and sustainable development of the cultural and creative industries of museums in China.